2008
DOI: 10.1177/1043986208319456
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of “Three Strikes and You're Out” on Crime Trends in California and Throughout the United States

Abstract: Her current research interests include racial and ethnic disparities in felony sentencing, and the effects of prosecutorial discretion on the implementation and impacts of Three Strikes. Impacts of "Three Strikes and You're Out" on Crime Trends in California and throughout the United States

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…In the United States, for example, community programs such as DARE (Drug Abuse Resistance Education) received billions of dollars in funding before proper evaluations showed they were ineffective (Greenwood 2006). Similarly, the profound monetary and social costs of three strikes laws and other mandatory sentencing strategies are now causing American policy makers to rethink such ''tough-on-crime'' measures (see Tonry 2009Tonry , 2006Sutton 2013;Western and Muller 2013;Cook and Roesch 2012;Kovandzic, Sloan, and Vieraitis 2004;Chen 2008). In Canada, we ignore the results of such research at our peril.…”
Section: Resultsmentioning
confidence: 99%
“…In the United States, for example, community programs such as DARE (Drug Abuse Resistance Education) received billions of dollars in funding before proper evaluations showed they were ineffective (Greenwood 2006). Similarly, the profound monetary and social costs of three strikes laws and other mandatory sentencing strategies are now causing American policy makers to rethink such ''tough-on-crime'' measures (see Tonry 2009Tonry , 2006Sutton 2013;Western and Muller 2013;Cook and Roesch 2012;Kovandzic, Sloan, and Vieraitis 2004;Chen 2008). In Canada, we ignore the results of such research at our peril.…”
Section: Resultsmentioning
confidence: 99%
“…Even though increased lengths of stay could be attributed to increased security levels, new treatment modalities, or enhanced risk assessment instruments, the rationale for initiating many such programs is often public demand for accountability and increased safety, similar to the impetus for tough on crime initiatives. It appears that although the get-tough-on-crime approach may not have had the intended punitive effect on correctional sentencing practices (Jacobson, 2006;Stolzenberg & D'Alessio, 1997), albeit the possibility of a potential modest deterrent effect for homicide rates (Chen, 2008;Kovandzic et al, 2004), it has affected, perhaps as an unintended consequence, those defendants that mount a successful affirmative defense of insanity and are indefinitely committed to one of Missouri's public psychiatric hospitals, as well as affecting all such acquittees, not simply those acquitted for murder.…”
Section: Discussionmentioning
confidence: 99%
“…Another future research direction should focus on whether states begin to refine insanity statutes that require lengthy or indefinite hospital commitments postacquittal given decreasing state operating budgets, in the same pattern as those states who may reconsider three strikes legislation due to skyrocketing operating costs, as have Mississippi and Louisiana (Chen, 2008;Jacobson, 2006;Kovandzic et al, 2004). This is an important line of research as a critical component of such commitments is the release process.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have repeatedly confirmed the success of automated traffic cameras in reducing both speeding and collisions (Wilson et al, 2010), indicating that policies to install traffic cameras can attain a stated objective of reducing vehicle accidents while also achieving distributional benefits of greater safety for motorists and pedestrians. In another example, 'tough on crime' legislation, which includes mandatory minimum sentences and 'threestrikes-you're-out' laws, has proven to be very popular among voters in many jurisdictions (Frost, 2010), despite numerous evaluation studies questioning its effectiveness in achieving crime reduction objectives (Chen, 2008;Cook and Roesch, 2012;Turner et al, 1999) and despite documented negative distributional outcomes for minority communities in some countries (Cook and Roesch, 2012;Newell, 2013). And more famously, state-endorsed abuses of civil rights, such as the various Jim Crow laws in the US states, achieved their policy goals of repression, segregation and discrimination, but were obviously detrimental to the populations they targeted.…”
Section: Introductionmentioning
confidence: 96%